2013
DOI: 10.3389/fpsyg.2013.00512
|View full text |Cite
|
Sign up to set email alerts
|

Serial binary interval ratios improve rhythm reproduction

Abstract: Musical rhythm perception is a natural human ability that involves complex cognitive processes. Rhythm refers to the organization of events in time, and musical rhythms have an underlying hierarchical metrical structure. The metrical structure induces the feeling of a beat and the extent to which a rhythm induces the feeling of a beat is referred to as its metrical strength. Binary ratios are the most frequent interval ratio in musical rhythms. Rhythms with hierarchical binary ratios are better discriminated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Perceiving rhythm also leads to phase-dependent facilitation for many aspects of auditory perception and cognition [ 49 ]. Rhythm-perceptual effects may lead to more economical storage of intervals at the expense of precision [ 50 ], similar to ‘lossy compression’, configural or familiarity effects observed in visual memory [ 51• , 52 ].…”
Section: Stm For Timementioning
confidence: 99%
“…Perceiving rhythm also leads to phase-dependent facilitation for many aspects of auditory perception and cognition [ 49 ]. Rhythm-perceptual effects may lead to more economical storage of intervals at the expense of precision [ 50 ], similar to ‘lossy compression’, configural or familiarity effects observed in visual memory [ 51• , 52 ].…”
Section: Stm For Timementioning
confidence: 99%
“…E-mail: nora.schaal@uni-duesseldorf.de the internal clock by Povel and Essens (1985); in the Generative Theory of Tonal Music by Lerdahl and Jackendorff (1983)). Many studies have examined the hierarchical structures of rhythm sequences and found that several factors influence rhythm reproduction (Drake, 1993;Drake, Penel, & Bigand, 2000;Wu, Westanmo, Zhou, & Pan, 2013). For example, Drake (1993) showed that binary rhythms (compared to ternary subdivisions), having two different durations in one sequence (by contrast to three durations), accents on important beats and the possibility to segment into shorter sequences, lead to better performance for rhythm reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…Third, perhaps the preponderance of duple meter in Western music means that the regularity manipulation was not as effective for triple groupings. Western listeners favor duple interpretations of rhythmic sequences (Bergeson & Trehub, 2006; Smith & Cuddy, 1989; Snyder, Hannon, Large, & Christiansen, 2006; Wu, Westanmo, Zhou, & Pan, 2013), so their relative lack of familiarity with triple metrical structures made them sound irregular, even when they were actually regular. This could explain why the regularity manipulation only worked for duple groupings.…”
Section: Discussionmentioning
confidence: 99%